The Using of Short Stories to Enhance Students’ Reading Comprehension - Yustina Jeni (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
The study uses classroom action research. This study also to solve the problems in the class and it also has a cycle with four steps. The data were collected by observation, learning test results, and documentation. This study involved 35 students in eight grade of SMPN 5 Samarinda. This study was carried out in one cycle. It also showed that there is an enhancement in students’ learning results. In addition, it can be said that the use of short stories during the teaching and learning process is very effective to enhance students’ reading comprehension. This is due to the enthusiasm of students to join the process and short stories that are exciting to read. Hence, the students’ mean score indicated that there is an enhancement during the teaching and learning process using short stories. Using short stories as teaching material and strategy in teaching is a very good way, especially to enhance their reading comprehension. This is because short stories provide motivation through moral lessons and get students involved in learning activities. Short stories also give students time to interact with the text by reading the whole story from various short stories. Besides, short stories are also exciting because short stories are very diverse and it enriches students’ vocabulary. Finally, short stories also make students think critically through what is conveyed by the stories.